IT Governance Capability Assessment Using COBIT 2019 DSS Domain: A Case of DKI Jakarta Education Office - Yasmin Hakim; Zaldy Adrianto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
As a provider of digital education services, the DKI Jakarta Provincial Education Office requires effective information technology (IT) governance to support the implementation of the Electronic-Based Government System (SPBE). However, the current SPBE evaluation does not assess the capability of IT processes at the operational level. Therefore, this study aims to: (1) assess the capability level of information technology governance within the Deliver, Service, and Support (DSS) domain using the COBIT 2019 framework, (2) analyze the gap between the current capability level (as-is) and the target capability level (to-be), (3) identify weaknesses in information technology service processes based on the capability assessment and gap analysis, and (4) formulate recommendations to improve information technology service governance. A qualitative approach with a case study method was employed. Data were collected through interviews, observations, and document analysis involving five informants selected using purposive sampling based on the RACI chart. The data were analyzed using the Process Assessment Model (PAM) to determine the capability level of each DSS process. The results indicate that DSS01, DSS04, DSS05, and DSS06 achieved Capability Level 3 (Established Process), while DSS02 and DSS03 achieved Capability Level 2 (Managed Process). Gap analysis revealed that all DSS processes remain below the target Capability Level 4 (Predictable Process), primarily due to the absence of quantitative process performance measurement, inadequate operational documentation, and insufficient monitoring and control mechanisms. The identified capability gaps reveal weaknesses in IT service processes, including the absence of standardized incident and problem management procedures, limited quantitative performance measurement, inadequate process control mechanisms, and incomplete operational documentation. Based on these findings, this study recommends developing Standard Operating Procedures (SOPs), establishing Key Performance Indicators (KPIs), and strengthening monitoring, control, and cross-unit coordination mechanisms to improve the quality of IT service governance. The findings also demonstrate that COBIT 2019 complements SPBE evaluation by providing a detailed operational-level capability assessment that supports continuous improvement of digital public services.